Stages of Designing A System for Improving the Mechanism for the Development of Valeological Competence in Future Teachers - Sardorkhon Kuvondikov (Scientific Trends, 2025)
This article used the criteria and indicators for the development of the competence of civil and national pride in future teachers as indicators of the assessment of upbringing in the introduction of the “concept of continuous spiritual education”. As a result, the possibility of diagnosing future educators in student’s readiness to form a competence of national pride has increased. These proposals made it possible to prepare future educators for educational activities, to develop an active civic position in them.
Keywords: Consciousness of national pride, patriotic worldview, spiritual-moral, civil-patriotic, military-patriotic, sports and patriotism, pedagogy.